The Induced Immune Response in Patients With Infectious Spondylodiscitis: A Prospective Observational Cohort Study - Loft, Josefine Amalie; Møller, Dina Leth; Thudium, Rebekka Faber; Knudsen, Jenny Dahl; Ostrowski, Sisse Rye; Andersen, Åse Bengård; Nielsen, Susanne Dam (Frontiers in Immunology, 2022)
Introduction: Infectious spondylodiscitis is a rare infection of the intervertebral disc and the adjacent vertebral bodies that often disseminates and requires long-term antibiotic therapy. Immunologic profiling of patients with infectious spondylodiscitis could allow for a personalized medicine strategy. We aimed to examine the induced immune response in patients with infectious spondylodiscitis during and after antibiotic therapy. Furthermore, we explored potential differences in the induced immune response depending on the causative pathogen and the dissemination of the disease. Methods: This was a prospective observational cohort study that enrolled patients with infectious spondylodiscitis between February 2018 and August 2020. A blood sample was collected at baseline, after four to six weeks of antibiotic therapy (during antibiotic therapy), and three to seven months after end of antibiotic therapy (post-infection). The induced immune response was assessed using the standardized functional immune assay TruCulture®. We used a panel of three immune cell stimuli (lipopolysaccharide, Resiquimod and polyinosinic:polycytodylic acid) and an unstimulated control. For each stimulus, the induced immune response was assessed by measuring the released concentration of Interleukin (IL)-1β, IL-6, IL-8, IL-10, IL-12p40, IL-17A, Interferon- γ (IFN-γ) and Tumor necrosis factor-α (TNF-α) in pg/mL. Results: In total, 49 patients with infectious spondylodiscitis were included. The induced immune responses were generally lower than references at baseline, but the cytokine release increased in patients after treatment with antibiotic therapy. Post-infection, most of the released cytokine concentrations were within the reference range. No significant differences in the induced immune responses based on stratification according to the causative pathogen or dissemination of disease were found. Conclusion: We found lower induced immune responses in patients with infectious spondylodiscitis at baseline. However, post-infection, the immune function normalized, indicating that an underlying immune deficiency is not a prominent factor for spondylodiscitis. We did not find evidence to support the use of induced immune responses as a tool for prediction of the causative pathogen or disease dissemination, and other methods should be explored to guide optimal treatment of patients with infectious spondylodiscitis.